Parent–practitioner engagement in early education and the threat of negative thinking about the poor across England and the USA. (May 2021) - Simpson, Donald; Mazzocco, Philip; Loughran, Sandra; Lumsden, Eunice; Clark, Rory McDowall; Winterbottom, Christian
Parent–practitioner engagement in the early years has become a key policy in remediating the negative effects of poverty upon children's early educational outcomes. Although this approach is shared across several developed countries, there has been limited attention upon how practitioners think about poverty and their engagement with parents in poverty. Our mixed methods study in England and the USA provides rare evidence addressing these issues. Among our practitioners in both countries 'parent blame' for poverty featured to some extent in the accounts of a majority of practitioners. We also found a relationship between the extent to which our practitioners felt individual parents are culpable for poverty and their reporting of more negative engagement with parents – particularly in England. We claim this is worthy of further study as a potential threat to the 'child–parent–practitioner triangle' and to remediation of poverty's effects within early educational contexts.